2021
DOI: 10.1108/ijchm-06-2021-0707
|View full text |Cite
|
Sign up to set email alerts
|

Who is an evangelist? Food tourists’ positive and negative eWOM behavior

Abstract: Purpose This study aims to examine food tourists’ engagement in positive and negative electronic word-of-mouth (eWOM) by considering the following questions: Do satisfied customers engage in advocacy, and do dissatisfied customers make the same effort to spread their negative experiences? Which restaurant experience attributes influence eWOM behavior? What demographic and psychographic characteristics contribute to advocacy? Design/methodology/approach Using data from an online survey of 456 consumers with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
(97 reference statements)
2
48
0
2
Order By: Relevance
“…Second, it further examines how work-related rumination mediates the effects of a lodging recovery experience on well-being. Moreover, as lodging businesses rely on customer satisfaction to produce repurchases or positive word-of-mouth (Kim and Hwang, 2021), the third purpose is to unveil the interrelationships of guest satisfaction with lodging recovery experience, work-related rumination and well-being. Finally, given that bed-and-breakfasts (B&B) are a popular type of lodging worldwide (So et al, 2021), this research also compares the structural relationships of the constructs between the hotel and B&B guests.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it further examines how work-related rumination mediates the effects of a lodging recovery experience on well-being. Moreover, as lodging businesses rely on customer satisfaction to produce repurchases or positive word-of-mouth (Kim and Hwang, 2021), the third purpose is to unveil the interrelationships of guest satisfaction with lodging recovery experience, work-related rumination and well-being. Finally, given that bed-and-breakfasts (B&B) are a popular type of lodging worldwide (So et al, 2021), this research also compares the structural relationships of the constructs between the hotel and B&B guests.…”
Section: Introductionmentioning
confidence: 99%
“…eWOM also articulates and strengthens a consumer's personality when he or she shares advertisements that are consistent with his or her personality (Taylor et al, 2012 ). However, few studies have demonstrated what factors compel consumers to create different types of eWOM (Hu and Kim, 2018 ; Nam et al, 2020 ; Sohaib et al, 2020 ; Kim and Hwang, 2022 ). Hu and Kim ( 2018 ) have found that there are different motivations behind positive eWOM and negative eWOM.…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%
“…Sohaib et al ( 2020 ) have found that promotion-focused customers are more likely to spread positive eWOM, while prevention-focused customers are more likely to spread negative eWOM. Kim and Hwang ( 2022 ) have found that authenticity is influential for positive eWOM only, and value is influential for negative eWOM only. However, no research has been conducted to explore the emotional factors that lead to different types of eWOM.…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%
See 2 more Smart Citations